The Impact on Industrial Estate Development Policy to Employment Absorption of West Java Province - Winardi Winardi; Dominicus Savio Priyarsono; Hermanto Siregar; Heru Kustanto (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
Development of industrial estates in the region have a role as a driver of the regional economy and will attract industrial companies to be located in the industrial estates so it will give most multiplier effect in the region’s economic growth. The purpose of this research is to analyze the impact of industrial estate development on employment absorption in West Java Province. In this research, the Social Accounting Matrix (SAM) model had been used by desegrating it to industrial manufacturing sector inside industrial estate. The result of analysts indicates that the industrial estate development policy through investment has an impact to the rise of creating broad employement opportunities or creating greater employment opportunities in both the industry itself and in other production sectors.